Analysis of Long-Term Spatio-Temporal Trends in Land Use/Land Cover in Devikulam Taluk, Kerala Using Geospatial Techniques - Solanki, Srishti; Chandran, Chindu; Garg, J.K.; Bhattacharya, Prodyut (International Journal of Environment, 2019)
This study was undertaken to evaluate the spatial as well as the temporal changes in land use/ land cover in Devikulam Taluk, Idukki District, Kerala, and to assess the effects of increasing anthropogenic pressure on the fragile ecosystem of this area. For analysis, land use/ land cover maps of four different years, i.e., 1988, 1999, 2008 and 2017, were generated using LANDSAT TM (Thematic Mapper), ETM+ (Enhanced Thematic Mapper Plus) and OLI/TIRS (Operational Land Imager/Thermal InfraRed Sensor) satellite imagery. The results of the study suggested that there has been a drastic increase in the built-up area and a continuous decline in the forest area in Devikulam from 35.31 km2 built-up in 1988 to 73.92 km2 in 2017, and 1374.52 km2 forest in 1988 to 1247.24 km2 in 2017, respectively. Over this period of approximately 40 years, around 47.85 km2 area of the forest got converted to built-up. This could be due to the increasing anthropogenic pressure in terms of migration or booming tourism contributing to the increased demand for infrastructures. Therefore, appropriate land use planning is a fundamental step towards the sustainable development of this biogeographically rich and unique area of Devikulam Taluk.